Sustainable development of cement mortars: A review of palm kernel shell-based admixtures and pre-hydration technique - Abdel Jabbar, Haneen; Rahimah, Embong; Fadzil, Mat Yahaya; Al Biajawi, Mohammad I. (Polska Akademia Nauk, 2025)
This review explores sustainable cement mortar production by examining palm kernel shells (PKS) as admixtures and the application of pre-hydration techniques. The environmental impact of traditional cement necessitates alternative materials. PKS, an agricultural waste product, offers a potential solution due to its availability and pozzolanic properties. Pre-hydration, involving controlled water addition before mixing, further improves mortar performance and reduce cement consumption. The results shows that PKS-based admixtures, when combined with pre-hydration technique, improve mortar strength, durability, and sustainability while reducing environmental impact. Future research should aim to optimize the PKS and pre-hydration techniques for various applications, and investigate the ability to use these methods in large-scale construction projects. These developments could lead to a more sustainable construction industry.